PERANCANGAN DAN IMPLEMENTASI APLIKASI PROFIL DESA BERBASIS WEBSITE (Studi Kasus: Desa Adibaboi Kabupaten Manokwari): DESIGN AND IMPLEMENTATION OF A WEBSITE-BASED VILLAGE PROFILE APPLICATION (Case Study: Adibaboi Village, Manokwari Regency) - Syahril Heremba; Christian Dwi Suhendra; Lion Ferdinan Marini (JISTECH: Journal of Information Science and Technology, 2023)
This research aims to design and implement a website-based village profile application, with a case study in Adibaboi Village, Manokwari Regency. This application is designed to help Adibaboi Village in introducing the village profile online, connecting the community with the village government, and making it easier to access information related to Adibaboi Village. The method used in this research is a software development method using the waterfall model, which consists of requirements analysis, design, implementation, testing and maintenance stages. The research results show that this website-based village profile application can be accessed by the public via the internet and has features such as information on village history and culture, village activities and agendas, organizational structure, list of officials and contacts, as well as village location maps. This application is expected to increase information openness and transparency of village government, as well as help the community to gain access to information related to Adibaboi Village more easily and effectively.